1994
DOI: 10.2307/1243920
|View full text |Cite
|
Sign up to set email alerts
|

Pricing to Market with Transactions Denominated in a Common Currency

Abstract: We present a model with two exporters who ship a differentiated commodity to the same import destination. All pricing occurs in a common currency, that of the home exporter. We show that the foreign-exporter to home-exporter exchange rate can influence the home exporter's pricing decision. It has been previously argued that only the importer to home-exporter exchange rate matters to the home exporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 8 publications
1
26
2
Order By: Relevance
“…In general, we found less PTM for Russian wheat exporters than other studies for the USA and Canada (e.g. Pick and Park, 1991; Pick and Carter, 1994; Jin, 2008; Jin and Miljkovic, 2008). There are several reasons why the pricing behaviour of Russian wheat exporters might differ from their competitors, the USA and Canada, reported by previous studies.…”
Section: Estimation Results and Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In general, we found less PTM for Russian wheat exporters than other studies for the USA and Canada (e.g. Pick and Park, 1991; Pick and Carter, 1994; Jin, 2008; Jin and Miljkovic, 2008). There are several reasons why the pricing behaviour of Russian wheat exporters might differ from their competitors, the USA and Canada, reported by previous studies.…”
Section: Estimation Results and Discussioncontrasting
confidence: 69%
“… Source: Own compilation based on Pick and Park (1991), Pick and Carter (1994), Carew and Florkowski (2003), Lavoie (2005), Jin (2008), Jin and Miljkovic (2008), USDA (2010), World Bank (2009) and own results. …”
Section: Estimation Results and Discussionmentioning
confidence: 99%
“…Recent studies have shown that this is a problematic assumption (Abbott and Kallio (1996), Pick and Carter (1994), and Veeman et al (1999). Much of the world grain trade controlled by five multinationals -including Cargill and Louis Dreyfus, international grain traders frequently 'price to market.'…”
Section: Trade Friction In the North American Market For Wheatmentioning
confidence: 99%
“…Knetter's model has since been used extensively, due to its simplicity and data availability, to determine the presence of price discrimination in international trade. This approach has been particularly popular in the study of food and agricultural exports (e.g., Pick and Park 1991;Pick and Carter 1994;Griffith and Mullen 2001;Carew and Florkowski 2003;and Glauben and Loy 2003), automobile exports (e.g., Knetter 1989Knetter , 1993Marston 1990;Gagnon and Knetter 1995), and in a wide range of other industries.1…”
Section: Pricing-to-market: Price Discrimination or Product Differentmentioning
confidence: 99%